Perlindungan Hukum Terhadap Ekosistem Mangrove Sebagai Upaya Mitigasi Perubahan Iklim - Hardiyanto Pono; Kaharuddin Kaendo; Sutriana Sutriana (INDO PUBLISHING, 2026)
Mangrove ecosystems play a strategic role in climate change mitigation due to their ability to absorb and store substantial amounts of blue carbon, as well as protect coastal areas from abrasion, tidal flooding, and sea-level rise. As the country with the largest mangrove area in the world, Indonesia possesses approximately 3.44 million hectares of mangrove forests, storing more than 3 billion tons of carbon reserves. This study aims to analyze the legal framework governing mangrove ecosystem protection within Indonesia’s environmental law system, examine the effectiveness of legal protection for mangroves as a climate change mitigation measure, and identify strategies for optimizing such legal protection. This research employs a normative legal research method using both the statutory approach and the conceptual approach, supported by primary and secondary legal materials obtained through library research. The findings reveal that the legal protection of mangrove ecosystems has been regulated through various laws and regulations, including Law Number 32 of 2009 on Environmental Protection and Management, Law Number 27 of 2007 in conjunction with Law Number 1 of 2014 on the Management of Coastal Areas and Small Islands, as well as several national policies related to mangrove management. However, the effectiveness of their implementation remains constrained by various challenges, including land-use conversion, weak law enforcement, and inadequate inter-agency coordination. Therefore, strengthening regulations, enhancing monitoring and law enforcement mechanisms, integrating climate change policies with mangrove management, and increasing community participation are necessary to ensure the sustainability of mangrove ecosystems as an effective instrument for climate change mitigation.